PHARMACOGENETIC VARIATIONS RELATED TO CLOPIDOGREL RESISTANCE AND ITS CLINICAL IMPLICATIONS: AN ISSUE WHICH REMAINS LARGELY UNADDRESSED - SABREEN BASHIR; R, Poornima (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Antiplatelet therapy with either clopidogrel alone or in combination with aspirin is the mainstay prophylactic drug therapy following percutaneous coronary intervention and long-term prevention of cardiovascular and cerebrovascular events. Non-responders/semi-responders to clopidogrel are reported to have increased incidences of adverse outcomes like recurrent ischemic attacks. Variability in response to clopidogrel is more common among Asians, and it is as high as 70% in some of the Asian communities. Researchers attribute inter-individual variations in response to clopidogrel to various pharmacogenetic determinants. Polymorphisms of multidrug resistance protein 1, CYP2C19 and its alleles, P2Y adenosine diphosphate (ADP) receptor are concluded to be specific to clopidogrel resistance in Indian population. Methods: A thorough literature search was done use different keywords such as clopidogrel resistance, pharmacogenomics, pharmacogenetic variability, and ethnic variability from database sources such as Google Scholar, Medline, PubMed Central, and Scopus. Results and Conclusion: Literature revealed a disparity between various pharmacogenetic determinants of clopidogrel resistance, particularly in the Asian population. Few studies suggest that there is no significant association between clopidogrel response variability and ADP receptor P2Yand P2Y gene polymorphisms. Variation in the cytochrome P450 2C19 (CYP2C19) gene coding for the CYP2C19 enzyme, involved in metabolism and conversion of the clopidogrel to active metabolites is considered one of the major determinants of clopidogrel resistance in some populations. Pooled data from various studies suggest that variability in clopidogrel response cannot be attributed to a single gene polymorphism and is thought to be multifactorial. However, disparity in the data related to the specific gene polymorphisms responsible for the encountered clopidogrel resistance necessitates the further evaluation of genome. 12 Keywords: Clopidogrel, Clopidogrel resistance, Single gene polymorphisms, Inter-individual variability. 1 , and P2Y 121